SOSIALISASI PENTINGNYA MENJAGA KEBERSIHAN LINGKUNGAN: Socialization Of The Importance Of Maintaining A Clean Environment - Aminullah, Aminullah; Apriani, Titin; Titawati, Titin; Sumahiradewi, Luh Gede; Hamid, Hamid; Astuti, Ni Kadek Puji; Nufus, Chairun; Tarmizi, Azhari (Yayasan Al-Amin Qalbu, 2025)
The purpose of implementing community service is to socialize the importance of maintaining environmental cleanliness to increase public awareness regarding the impact of an unclean environment and provide an overview of waste management and directly clean the environment. The method for realizing community service activities is